2001
DOI: 10.1080/09687680010026313
|View full text |Cite
|
Sign up to set email alerts
|

Recent molecular advances in studies of the concentrative Na+-dependent nucleoside transporter (CNT) family: identification and characterization of novel human and mouse proteins (hCNT3 and mCNT3) broadly selective for purine and pyrimidine nucleosides (system cib)

Abstract: The human concentrative (Na+-linked) plasma membrane transport proteins hCNT1 and hCNT2, found primarily in specialized epithelia, are selective for pyrimidine nucleosides (system cit) and purine nucleosides (system cif), respectively. Both have orthologs in other mammalian species and belong to a gene family (CNT) that also includes members in lower vertebrates, insects, nematodes, pathogenic yeast and bacteria. The CNT transporter family also includes a newly identified human and mouse CNT3 transporter isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 0 publications
1
84
0
3
Order By: Relevance
“…It has been shown that modulation of cellular enzymes of gemcitabine transport and metabolism influences drug activity in vitro (Mackey et al, 1998(Mackey et al, , 1999Goan et al, 1999;Ritzel et al, 2001). Cellular enzymes of gemcitabine transport and metabolism, that is, hENT1, dCK, RRM1, and RRM2, are well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that modulation of cellular enzymes of gemcitabine transport and metabolism influences drug activity in vitro (Mackey et al, 1998(Mackey et al, , 1999Goan et al, 1999;Ritzel et al, 2001). Cellular enzymes of gemcitabine transport and metabolism, that is, hENT1, dCK, RRM1, and RRM2, are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies performed on human cancer cell lines, human equilibrative nucleoside transporter-1 (hENT1) was found to be the major gemcitabine transporter (Garcia-Manteiga et al, 2003). If gemcitabine is not transported into the cell via hENT1 it cannot inhibit cell growth (Mackey et al, 1998;Rauchwerger et al, 2000), but increased hENT1 abundance facilitates efficient cellular entry of gemcitabine and confers increased cytotoxicity (Mackey et al, 1999;Ritzel et al, 2001). Inside the cell, gemcitabine is phosphorylated by deoxycytidine kinase (dCK) in a rate-limiting step.…”
mentioning
confidence: 99%
“…Moreover, our results are in line with previous reports that suggested a common nucleoside transport system for 5-azaCyd as well as cytidine and uridine with similar efficiency (33). Further studies are required to determine whether additional hCNT proteins, such as hCNT3 (34), can also mediate 5-azaCyd transport.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ENTs, CNTs demonstrate some substrate specificity [43,335] (Table 1). CNT1 transports pyrimidine nucleosides and to some degree, Ado, CNT2 transports purine nucleosides and Urd, while CNT3 transports both classes with the ability to create a 10-fold higher concentration gradient due to 2:1 Na + -nucleoside coupling, suggesting that it might play a role under special circumstances [336]. There are fewer compounds available for the inhibition of concentrative nucleoside transporters than for equilibrative nucleoside transporters.…”
Section: Recently Developed Drugs Acting On the Adenosinergic System mentioning
confidence: 99%